USM STUDENT WINS ULDP 2016 CEO CHALLENGE, CREATES "ON MY WAY" APPLICATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 3 September 2016 Universiti Sains Malaysia (USM) student from the School of Management, Jocelyn Lim Jia Sin, 21, has made the university proud in winning the Fourth Axiata University Leadership Development Programme (ULDP) 2016 for its CEO Challenge together with her teammates.